Semantic Web, ontologies and GIS for the cultural routes - Annarita Orsini; Alessio Innocenti (Netcom)
Cultural routes have become more and more successful touristic destinations all around Europe. In 2016, the Italian Ministry of Cultural Heritage and Activities and Tourism (MiBACT), announced “The Year of Walking”, in order to promote cultural itineraries and “slow” tourism. Thanks to this opportunity, the DG-Tourism could list all the Italian cultural routes and elaborate then some projects about digitalization in tourism. There are two main projects going on : the first one is the elaboration of an ontology for the domain “Cultural Routes”, looking forward the innovations introduced by the Semantic Web ; the second one is the role of the GIS software in the field of management of the cultural routes.